Pengenalan Ruang Terbuka Hijau (RTH) dan Ruang Terbuka Non-Hijau (RTNH) : Indonesian - Muh Azhari; Fahruddin Arfianto; Pienyani Rosawanti; Putri Irianti Sintaman (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
Palangka Raya City is one of the cities that is experiencing growth and development along with the increasing number of residents occupying the area. The city of Palangka Raya with its environmental conditions must managed by paying attention to sustainability aspects and thinking about the risks of its management, for example the management of Green Open Space and Non-Green Open Space in the area. Apart from the government managing the environment, the community must also be able to maintain and manage the environment which has been designated for certain conditions. so that the environment remains well managed. for example by involving students as part of service activities, because students can become vioners and agents of change. Community service activities carried out using observation techniques and case studies at RTH and RTNH locations can improve and have an influence in protecting the environment in accordance with the established functions. The functions of RTH and RTNH include educational functions, tourism functions, economic functions and aesthetic functions and ecological functions.